Discovering the Underlying Motivations for Empowering Education Through Innovation - Maspul, Kurniawan Arif (Journal of Information System and Education Development, 2024)
Educational innovation has evolved as a revolutionary response to traditional teaching methods' limitations in educating pupils for the complexities of today's society. This method integrates technology, global viewpoints, and inclusive practices, motivated by the need to stimulate creativity, critical thinking, and collaboration. Education can build dynamic learning environments that encourage students to become active participants in their education by embracing innovation. This article investigates the incentives that drive educational innovation, emphasizing the importance of technological integration, leadership, global viewpoints, and inclusivity. This study provides valuable insights for educational practitioners, policymakers, and researchers through discussions, observations, and a comprehensive literature review, emphasizing the importance of embracing innovation to meet the evolving needs of students and prepare them for a rapidly changing future.